Electronic and photonic reactive collisions in edge fusion plasma and interstellar space: Application to H2 and BeH systems. (15th January 2015) - Mezei, J Zs; Niyonzima, S; Backodissa, D; Pop, N; Tamo, F O Waffeu; Chakrabarti, K; Motapon, O; Wolf, A; Robert, J; Dulieu, O; Larson, Å; Orel, A E; et al.
Abstract: Reactive collisional and radiative elementary processes rate coefficients have been either computed using multichannel-quantum-defect theory methods, or measured in merged-beam (storage ring) and crossed-beam experiments. The reaction mechanisms are explained and output data are displayed in ready-to-be-used form, appropriate for the modeling of the kinetics of the edge fusion plasma and of the interstellar molecular clouds.